Structural and electrical investigations of MBE-grown SiGe nanoislands - YANIK, SERHAT (SPRINGER HEIDELBERG, 2018)
SiGe nanoislands were grown by Molecular Beam Epitaxy (MBE) method on Si (100) substrates with comparative growth parameters such as annealing temperature, top Ge content and layer-by-layer annealing (LBLA). XRD and Raman data suggest that annealing temperature, top Ge content and layer-by-layer annealing (LBLA) can overall give a control not only over the amorphous content but also over yielding the strained Ge layer formation in addition to mostly Ge crystallites. Depending on the layer design and growth conditions, size of the crystallites was observed to be changed. Four Point Probe (FPP) Method via Semiconductor Analyzer shows that 100 degrees C rise in annealing temperature of the samples with Si0.25Ge0.75 top layers caused rougher islands with vacancies which further resulted in the formation of laterally higher resistive thin film sheets. However, vertically performed I-AFM analysis produced higher I-V values which suggest that the vertical and horizantal conductance mechanisms appear to be different. Ge top-layered samples gained greater crystalline structure and better surface conductivity where LBLA resulted in the formation of Ge nucleation and tight 2D stacking resulting in enhanced current values.
Keywords: GE-ON-SI; QUANTUM DOTS; GERMANIUM; NANOSTRUCTURES; STRAIN; GAAS; DEVICES